How 1,n-Bis(3-alkylimidazolium-1-yl) Alkane Interacts with the Phospholipid Membrane and Impacts the Toxicity of Dicationic Ionic Liquids - Kaur, Navleen (Langmuir : the ACS journal of surfaces and colloids, 2022)
Ionic liquids based on doubly charged cations, often termed dicationic ionic liquids (DILs), offer robust physicochemical properties and low toxicity than conventional monocationic ionic liquids. In this design-based study, we used solid-state NMR spectroscopy to provide the interaction mechanism of two DILs, 1,n-bis(3-alkylimidazolium-1-yl) alkane dibromide ([C2n(C7-nIM)2]2+·2Br-, n = 1, 6), with 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) and 1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-(1'-rac-glycerol) (POPG) phospholipid membranes, to explain the low toxicity of DILs toward HeLa, Escherichia coli, Bacillus subtilis, and Saccharomyces cerevisiae cell lines. Dications with a short linker and long terminal chains cause substantial perturbation to the bilayer structure, making them more membrane permeabilizing, as shown by fluorescence-based dye leakage assays. The structural perturbation is even higher than [C12(MIM)]+ monocations, which carry a single 12-carbon long chain and exhibit a much higher membrane affinity, permeability, and cytotoxicity. These structural details are a crucial contribution to the design strategies aimed at harnessing the biological activity of ionic liquids